SCRUTINIZING THE ROLE OF ARABIC IN SHAPING LITERACY IN INDONESIA - Pradi Khusufi Syamsu (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2017)
AbstractThis article concludes that Arabic has a very significant role in shaping the culture of literacy in Indonesia. Arabic influences Indonesian from script to semantic, lexicographic, and grammatical. Islam is synonymous with the Arabic language able to change the views of Indonesian people who originally oriented-art only with beautiful temples into a book-oriented manifestation with the creation of many writings in the form of manuscripts that were born thousands and even millions of manuscripts.This study is a literature study. The author uses two approaches in social sciences that are, historically, to know social, cultural and political phenomena; while the philology approach is used to find out Arabic Jawi manuscripts that are actually rich in unexpected information.Keywords: Arabic, Literacy, Manuscripts, Indonesia, Malay